2011
DOI: 10.1057/grir.2010.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Brokerage Commissions for Fair Insurance: A First Order Approach

Abstract: This paper studies a principal-agent insurance brokerage problem with a riskaverse principal (an insured) and a risk-neutral agent (a broker). The concept of "mean-preserving, spread-reducing" (MPSR) effort is introduced to model the broker's activities. Using the first-order approach, it is shown that under some common conditions, the insured may "concavify" the reward function to induce the risk-neutral agent to exert MPSR brokering effort. These conditions, together with an additional condition, guarantee t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…This agent has the authority to prepare and approve the principal's registration in advance, to negotiate on behalf of these rate and coverage conditions, whose final beneficiary is the insured (Pereira, 2017). The broker can make opportunistic use of the set of information of which disposes to the detriment of the insured's interests (e.g., reducing the price of insurance through limited coverage and/or directing the quote to an insurer that pays a higher commission) without fully meeting the requirements in this type of arrangement (Hau, 2011;Outreville, 2012). This condition can also lead to a secondary agency problem (SAP) when the broker acts in his interest without meeting the expectations of the principal that appointed him (Figure 2).…”
Section: Insurermentioning
confidence: 99%
“…This agent has the authority to prepare and approve the principal's registration in advance, to negotiate on behalf of these rate and coverage conditions, whose final beneficiary is the insured (Pereira, 2017). The broker can make opportunistic use of the set of information of which disposes to the detriment of the insured's interests (e.g., reducing the price of insurance through limited coverage and/or directing the quote to an insurer that pays a higher commission) without fully meeting the requirements in this type of arrangement (Hau, 2011;Outreville, 2012). This condition can also lead to a secondary agency problem (SAP) when the broker acts in his interest without meeting the expectations of the principal that appointed him (Figure 2).…”
Section: Insurermentioning
confidence: 99%
“…Esse agente, que está autorizado a elaborar e aprovar previamente o cadastro do tomador, a negociar em nome deste condições de taxa e de cobertura, cujo beneficiário final é o segurado (Pereira, 2017) pode fazer uso de forma oportunista do conjunto de informações de que dispõe em detrimento dos interesses do segurado (ex. : reduzindo o preço do seguro através de uma cobertura limitada e/ou direcionando à cotação para uma seguradora que paga uma comissão maior) sem contudo atender plenamente às exigências requeridas nesse tipo de arranjo (Hau, 2011;Outreville, 2012). Essa condição pode levar também a um problema de agência secundário (PAS), quando o corretor age em seu interesse próprio, sem atender às expectativas do tomador que o nomeou (Figura 2).…”
Section: Seguradoraunclassified
“…Fear of sickness, for example, is likely to feed a patient's aversion to downside risk as she interacts with her doctor/agent (Courbage and Rey 2006). Prudence might also characterize an insurance customer seeking advice from her broker/agent (Hau 2011). A regulator who adopts a precautionary stand -as it is the case in Europe and the United States in public health, food safety and environmental policy (Barrieu and Sinclair-Desgagné 2006, Wiener et al 2011) -was shown to exhibit prudent risk preferences (Gollier et al 2000).…”
Section: Introductionmentioning
confidence: 99%